Efektifitas Kewenangan Komisi Nasional Hak Asasi Manusia Terhadap Penyelesaian Pelanggaran Hak Asasi Manusia yang Berat di Indonesia - Sinaga, Alpases Pranoto Oktavianus; Riwanto, Agus (Res Publica: Jurnal Hukum Kebijakan Publik, 2022)
This research analyzes and examines the effectiveness of the authority of Komnas HAM in resolving cases of gross human rights violations in Indonesia. This research is a prescriptive normative legal research that aims to analyze the effectiveness of the authority of Komnas HAM in solving the problem of gross human rights violations and provide solutions to these problems. This research uses data types in the form of primary legal materials and secondary legal materials. Data collection is done through library research to find secondary data using primary, secondary, and tertiary legal materials. The author uses a statute-limitation approach, case concept, and history. The results show that Komnas HAM as an institution that is not given the authority to resolve the problem of gross human rights violations in the field of investigation does not cause obstruction in the settlement of cases of gross human rights violations in Indonesia, which is caused by the weak legitimacy of the settlement.